Facebook democracy : the architecture of disclosure and the threat to public life - Marichal, José. (London : Routledge, 2016)
Drawing on a number of disciplines and an ethnographic analysis of 250 Facebook political groups, Marichal explores how Facebook's emphasis on social connection impacts key dimensions of political participation: e.g. mobilization, deliberation, and attitude formation.
Introduction : the allure of facebook -- 1. Facebook and the utopian/dystopian dialectic -- 2. Facebook and the architecture of disclosure -- 3. Facebook and the decline of the public -- 4. The personal citizen -- 5. Engagement as personal citizens -- 6. The digital front stage and deliberation -- 7. Facebook and mobilization : beyond the Facebook revolution -- 8. Privacy in the age of personal politics -- 9. Friending the nation-state : social networking and power -- 10. Conclusions : how to listen on Facebook.
Originally published 2012 by Ashgate Publishing.
Includes bibliographical references (pages 161-188) and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Facebook (Firm); Facebook (Firm); Political participation -- Technological innovations; Communication in politics -- Technological innovations; Political participation -- Data processing; Disclosure of information; Online social networks -- Political aspects; Electronic books